Actinic cheilitis: a systematic review of treatment options. (26th December 2020) - Trager, M.H.; Farmer, K.; Ulrich, C.; Basset‐Seguin, N.; Herms, F.; Geskin, L.J.; Bouaziz, J.‐D.; Lebbé, C.; de Masson, A.; Bagot, M.; Dobos, G.
Abstract: Actinic cheilitis is a premalignant condition that can progress to squamous cell carcinoma with a higher propensity for metastasis than cutaneous squamous cell carcinoma. Optimal treatment for actinic cheilitis has not been established, and evidence‐based estimates of clinical cure in the dermatology literature are limited. Here, we review and synthesize outcome data published for patients with actinic cheilitis after treatment with various modalities. A systematic review was conducted in MEDLINE, Embase and the Cochrane library for English, French and German‐language studies and references of included articles from inception to 20 January 2020. Studies were included if they reported on at least six patients with biopsy‐proven actinic cheilitis. After quality appraisal, results of studies with the strongest methodology criteria were synthesized. 18 studies of 411 patients (published 1985 to 2016) were included. The majority of the studies were case series. Carbon dioxide laser ablation and vermilionectomy were associated with the most favourable outcomes with fewest recurrences. Chemical peel and photodynamic therapy were associated with higher recurrence. Adverse effects generally resolved in the weeks following treatment and cosmetic outcomes were favourable overall. In conclusion, there is a lack of high‐quality comparative studies evaluating different treatment options for actinic cheilitis. The included publications used various outcome measures; however, the majority reported on the recently defined core outcome sets. These results suggest that both carbon dioxide laser ablation and vermilionectomy are effective treatments for actinic cheilitis. Prospective head‐to‐head studies are needed to compare these treatment modalities and to assess patient preferences.